Structural racism theory, measurement, and methods: A scoping review - Wien, Simone; Miller, Andres L.; Kramer, Michael R. (Frontiers in Public Health, 2023)
Epidemiologic and public health interest in structural racism has grown dramatically, producing both increasingly sophisticated questions, methods, and findings, coupled with concerns of atheoretical and ahistorical approaches that often leave the actual production of health or disease ambiguous. This trajectory raises concerns as investigators adopt the term “structural racism” without engaging with theories and scholars with a long history in this area. This scoping review aims to build upon recent work by Adkins-Jackson et al. (2021) and Hardeman et al. (2022) by identifying current themes about the incorporation of thinking about structural racism into (social) epidemiologic research and practice with respect to theory, measurement, and practices and methods for trainees and public health researchers who are not already deeply grounded in this work. This review uses Arksey and O'Malley’s (2005) methodological framework and includes peer-review articles written in English published between January 2000-August 2022. A search of Google Scholar, manual collection, and referenced lists identified a total of 235 articles, 138 met the inclusion criteria after duplicates were removed. Results were extracted by, and organized into, three broad sections: theory, construct measurement, and study practice and methods, with several themes summarized in each section. This review concludes with a summary of recommendations derived from our scoping review and a call to action echoing previous literature to resist an uncritical and superficial adoption of “structural racism” without attention to already existing scholarship and recommendations put forth by experts in the field.